Ageing in Europe: Supporting policies for an inclusive society - Axel Börsch-Supan; Thorsten Kneip; Howard Litwin; Michał Myck; Guglielmo Weber (De Gruyter, 2015)
SHARE is an international survey designed to answer the societal challenges that face us due to rapid population ageing. How do we Europeans age? How will we do economically, socially and healthwise? How are these domains interrelated? The authors of this multidisciplinary book have taken a further big step towards answering these questions based on the recent SHARE data in order to support policies for an inclusive society.
Keywords: 330; Europe; Aging; Demography; Alternde Bevölkerung; Ältere Menschen; Soziale Integration; Soziale Ausgrenzung; Europa; EU-Staaten; Israel